Internet Technologies and Organizational Social Image: Interconnection and Real Potential - R. Khairullina , Elmira; V. Danilov , Anatoly; V. Romanova, Tatyana; I. Bogdanova, Venera; V. Slepneva, Elena; B. Pokaninova, Elena; G. Shubovich, Valery (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to analyze the impact of Internet technologies on the social image of organizations and identify the specifics of using Internet technologies as a necessary tool for forming the company's image. The following methods of research were used: the structural analysis method and the content analysis method, which allow us to determine the features of Internet technologies’ use and determine the trend in the use of corporate sites. The article considers the specifics of using Internet technologies as a necessary tool for forming the company's image, analyzes corporate websites of companies, determines the specifics of using Internet technologies in this context, and studies the use of social networks by organizations. The novelty and originality of the research lie in the fact that the essence of the concept image is considered in relation to commercial organization (a purposefully formed image of the organization having the character of a stereotype; a set of associations and impressions, which is developed in the mass consciousness of people and is associated with a particular representation). For the first time, the key factors that form a positive image of organizations in the field of business using Internet technologies are highlighted: information disclosure, artistic design, intuitiveness and functionality, and reliability and security. For the first time, modern Internet technologies are analyzed, and their specificity is determined on the example of commercial organizations; certain trends are identified related to the use and content of corporate sites (site design, user interface usability, website communicativeness); and the use of social networks. It is shown that the specifics of using Internet technologies by organizations in the banking sector are that these companies share channels of communication with the user: on the one hand, they actively promote their products and services on social media and also work to attract new subscribers by publishing interesting posts, videos, and tweets; on the other hand, they do not provide an opportunity for customers to evaluate their activities on the official corporate website. For the first time, it was determined that for the presentation of goods and services, organizations in the banking sector use interactive promo units, as well as sections with promotions and special offers from the bank. It is determined that almost all organizations in the banking sector have a press center; it is shown that its presence is an important criterion for evaluating the organization among clients and competitors. It is determined that the very name of this information service is the same on all the studied sites. It is revealed that commercial organizations selling household appliances actively use Internet technologies as a tool to increase loyalty and create a positive image among potential customers, partners, and competitors. It is determined that these organizations in the field of business focus on corporate sites using online store technologies and on promotion on social media in order to create a communication space with users.